Association between ambient air pollution and outpatient visits for primary acquired lacrimal duct obstruction in Hangzhou, China - Miao, Qi; Wang, Yuwei; Xu, Peifang; Shi, Xin; Wu, Yihua; Ye, Juan; Wu, Han (Frontiers in Public Health, 2025)
BackgroundPrimary acquired lacrimal duct obstruction (PALDO) is the most common lacrimal drainage disease in clinics, which can be caused by multiple factors. However, few studies have investigated environmental risk factors contributing to PALDO exacerbation. This study aimed to investigate the potential association between short-term exposure to major ambient air pollutants and outpatient visits for PALDO.MethodsData of outpatients with PALDO who visited the Eye Center of the Second Affiliated Hospital, Zhejiang University School of Medicine (Hangzhou, Zhejiang Province, China) from January 1, 2014 to December 31, 2022 were collected. The concentrations of particulate matter (PM10 and PM2.5), nitrogen dioxide (NO2), sulfur dioxide (SO2), carbon monoxide (CO) and ozone (O3), as well as the meteorological factors during the same period were obtained from Resource and Environment Science and Data Center, Chinese Academy of Science. A conditional logistic regression with a time-stratified case-crossover design was conducted to analyze the association between air pollutants and outpatient visits for PALDO.ResultsIn the single-pollutant model, significant associations were observed between PM10 (Odds ratio (OR) = 1.0022; 95% confidence interval (CI):1.0008, 1.004), PM2.5 (OR = 1.0025; 95% CI: 1.0004, 1.005), NO2 (OR = 1.006; 95% CI: 1.0025, 1.010), SO2 (OR = 1.0124; 95% CI: 1.0027, 1.022) and CO (OR = 1.3273; 95% CI: 1.0183, 1.73) and outpatient visits for PALDO. These associations remained significant after adjusting for the certain pollutant in the multi-pollutant model except NO2. Moreover, variations occurred between sexes, among different age groups and different seasons.ConclusionsOur study provided new and robust evidence that short-term exposure to air pollution may increase the risk of PALDO. Further studies are needed to decipher the underlying mechanisms.